The potential of quercetin in Psidium Guajava L. leaves extract as bioinhibitor for controlled released fertilizer - Ramli, N.K. (Trans Tech Publications Ltd, 2014)
This study was done to investigates the usage of natural products as one of the materials in fertilizer application. Urease inhibitors that are commonly used in agriculture are usually chemical based which affects the environment. Introducing natural products will ensure biodegradability of the material. Psidium Guajava L. (guava) has been reported to have properties such as antibacterial, anti-oxidant, anti-cancer, and anti ulcer for medical purposes. Guava leaves extract contains an active compound named quercetin that was successfully reported to exhibit significant urease inhibitory activities. Spectrophotometric method was used in this study with the theory of Beer's Law in order to measure the changes in ammonia concentration. Small reduction of ammonia (NH3) concentration with different about 0.1 mol/L was calculated and the releasing was almost equal till the end of incubation time. The guava leaves extract prepared showed the potential to reduce the release of NH3 concentration during urea application. Â© (2014) Trans Tech Publications, Switzerland.